Synthesis and Characterization of Some Mannich Bases as Potential Antimicrobial Agents - S. Chouhan, Hemendra; K. Singh, Sushil; Moorthy, N.S.H.N. (Asian Journal of Chemistry, 2010)
A series of Mannich base derived from the substituted acetophenone were synthesized under the acidic condition and evaluated for the antimicrobial activity by the disc diffusion method. Chemical structures of synthesized Mannich base were determined by FTIR, 1H NMR, FABMS spectroscopic analysis. The results showed that the Mannich bases were successfully synthesized under the acidic condition and compound 4 in the series possess the significant antimicrobial activity.